Analisis Jabatan dan Implikasinya Terhadap Kinerja Tenaga Pendidik - Nanda Silsabila Herawati; Putri Novita Ramadhani; Abdul Aziz; Mu’alimin Mu’alimin, (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research discusses job analysis and its implications for the performance of teaching staff. Job analysis is a crucial element in human resource management, because it helps organizations understand the tasks that must be performed in each position, set objective performance standards, and align individual goals with organizational goals. In addition, job analysis also supports career development, human resource planning, and ensures compliance with legal provisions related to occupational safety and health. In the educational context, job analysis is important to understand the duties and responsibilities of teaching staff in achieving educational goals in accordance with religious values. This research uses a literature review method to evaluate the impact of job analysis on the performance of teaching staff by referring to previous empirical studies. The results show that a clear understanding of duties and responsibilities can increase motivation, job satisfaction and overall performance of teaching staff.